Analysis of Employer Branding Transformation through Climate-Conscious HR Initiatives, Social Value Leadership, and Humanistic Work Design in Manufacturing Industry in East Java - Sono, Mohammad Gifari; Arisanti, Ivon; Muhtadi, Muhamad Ammar (West Science Social and Humanities Studies, 2025)
This study examines the role of climate-conscious HR initiatives, social value leadership, and humanistic work design in transforming employer branding in the manufacturing industry in East Java. Using a quantitative approach with a sample size of 170 respondents, data were analyzed through Structural Equation Modeling - Partial Least Squares (SEM-PLS) 3. The findings reveal that all three dimensions significantly enhance employer branding, with humanistic work design showing the strongest influence. The combined effect of these variables explains 68% of the variance in employer branding, highlighting the importance of an integrated approach. This research contributes to the Resource-Based View (RBV) theory and provides actionable insights for HR managers and industry leaders seeking to build sustainable and attractive employer brands in competitive markets.